P2 Voluntary cough suppression in chronic refractory cough and chronic obstructive pulmonary disease. (December 2018) - Cho, PSP; Fletcher, HV; Patel, IS; Jolley, CJ; Turner, RD; Birring, SS
Abstract : Introduction: Functional MR brain imaging data suggest a reduction in voluntary cough suppression may be an important mechanism underlying chronic refractory cough (CRC). Cough is a common symptom of COPD. The ability to suppress cough voluntarily in COPD is not known; a better understanding may yield an insight into the mechanisms of cough in COPD. We investigated voluntary cough suppression in COPD, CRC and healthy individuals. Methods: Participants underwent an incremental capsaicin challenge test (0.49–1000 µmol.L -1 ) and were instructed, 'please do not cough during the test'. Numbers of coughs provoked by each inhalation were recorded and the capsaicin concentrations required to elicit 5 coughs under suppression (CS5) were calculated by interpolation. Patients with COPD also completed cough severity and urge-to-cough visual analogue scales (VAS; 0–100 mm) over the past 1 week, and quality of life, Leicester Cough Questionnaire (LCQ; range 3–21). Results: 11 participants had COPD: median (IQR) age 67 (65–71) years; 6 (55%) female; FEV1 49 (43–69)% predicted, of whom 6 (55%) reported a chronic cough. There were 30 participants with CRC and 23 healthy controls: mean (SD) ages 59.9 (9.5) and 54.5 (11.6) years; 26 (87%) and 19 (83%) female, respectively. Median (IQR) cough severity VAS, 26 (11–50) mm; urge-to-cough VAS, 22 (12–66) mm and LCQ total score, 17 (13–20) in participants with COPD. Participants with COPD were more able to suppress cough than those with CRC: geometric mean (SD) CS5 87.58 (8.77) vs 4.94 (4.43) µmol.L -1 respectively; mean (95% CI) doubling dose difference 4.15 (2.41–5.89), p<0.01 (figure 1). There was no significant difference in cough suppression between COPD and healthy controls: geometric mean (SD) CS5 87.58 (8.77) vs 261.1 (4.34) µmol.L -1 ; mean (95% CI) doubling dose difference 1.58 (0.28–3.43), p=0.16. There was no significant association of CS5 with cough severity VAS (rho=−0.12), urge-to-cough VAS (rho=0.02) and LCQ (rho=0.07) in COPD, all p>0.75. Discussion: Patients with COPD were able to voluntarily suppress capsaicin-evoked cough; those with CRC were not. This novel finding supports previous work suggesting differences in the mechanisms of cough in the two conditions. Therapeutic interventions that enhance cough suppression should be considered for CRC patients.